The Interaction of Learning Model Implementation and Learning Motivation in Improving Critical Thinking Skills of Elementary School Students - Afrida, Fira Nadliratul; Rifai RC, Achmad; Utanto, Yuli (Journal of Primary Education, 2019)
This study has purpose to assess the interaction of the learning model (Problem Based Learning and Inquiry Based Learning) and learning motivation to improve the 21st century skills of elementary school students, particularly at the stage of critical thinking. The method applied was quantitative descriptive by interacting learning model, learning motivation to in improving the 21st century skill by using data analysis techniques of validity, reliability, level of difficulty, normality test, homogeneity test and two-way ANOVA. The data collection technique used in this study was in the form of technical tests of essay test and non-test in the form of motivation attitude scale and in-depth interview. Subjects in this study consisted of 64 students. They were divided into two groups, 32 students by using the learning model of PBL model and 32 students by using the learning model of IBL. These results of this study showed that; (1) There is no interaction between the learning model of (PBL and IBL) and learning motivation in improving the 21st century skill of elememtary students in their critical thinking skills. Based on the statistical analysis, obtained sig value higher than 0.05. (2) To improve the critical thinking of studnts, the learning model of PBL is better than the learning model of IBL. (3) The implementation of the learning model of (PBL and IBL) was able to increase students' motivation. (4) The increase of students' motivation with PBL learning model was higher than the IBL learning models.